1996
DOI: 10.1029/96ja01083
|View full text |Cite
|
Sign up to set email alerts
|

Variation of plasmatrough density derived from magnetospheric field line resonances

Abstract: The diurnal variation of ULF field line resonant frequencies has been calculated using the cross phase of data from the north‐south components recorded at seven latitudinally spaced ground magnetometers in the Canadian Auroral Network for the OPEN Program Unified Study (CANOPUS) array. CANOPUS magnetometers range in latitude from Rankin Inlet (L = 12.4) south to Pinawa (L =4.3). Using cold plasma MHD theory, an R−4 plasma density function, and the T87 magnetic field model, the variation of plasma density in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…Correspondingly, the calculations of Lotko et al (1998) give a frequency for the FLR near 11 mHz, assuming the plasma density in the equatorial plane is about 1 particle per c.c. Nevertheless, numerous observations (Samson et al, 1992a;Waters et al, 1996) indicate that the FLR frequency at this latitude is much lower, at times below 2 mHz. Chan et al (1994) have clearly shown that a stretched field topology in the magnetotail, associated with near-Earth (8−12 R E tailward) pressure gradients, can lead to FLR eigenmodes with much lower frequencies.…”
Section: Flr Eigenstructure and Eigenfrequencymentioning
confidence: 99%
“…Correspondingly, the calculations of Lotko et al (1998) give a frequency for the FLR near 11 mHz, assuming the plasma density in the equatorial plane is about 1 particle per c.c. Nevertheless, numerous observations (Samson et al, 1992a;Waters et al, 1996) indicate that the FLR frequency at this latitude is much lower, at times below 2 mHz. Chan et al (1994) have clearly shown that a stretched field topology in the magnetotail, associated with near-Earth (8−12 R E tailward) pressure gradients, can lead to FLR eigenmodes with much lower frequencies.…”
Section: Flr Eigenstructure and Eigenfrequencymentioning
confidence: 99%
“…For simplicity, we choose the density profile to be a power law (e.g. Waters et al, 1996) ρ=ρ eq (r/5) −4 , where r is measured in Earth radii, and ρ eq =7 amu/cm 3 . Detailed studies of the effect of the density distribution on the ULF wave frequencies have been conducted in the past (e.g.…”
Section: Eigenmode Equationsmentioning
confidence: 99%
“…The distribution and time variation of plasma density in the magnetosphere can be estimated from ground-based observations of ULF waves as standing waves of the Alfven mode (Obayashi and Jacobs, 1958;Waters et al, 1991Waters et al, , 1996. Theoretical work suggested the development of the field line resonance model of ULF waves (Tamao, 1966;Chen and Hasegawa, 1974;Southwood, 1974).…”
Section: Introductionmentioning
confidence: 99%